Español - Español; Español (Ars Pharmaceutica (Internet), 1978)
Studies made on 150 urine samples have shown the existence of the germ responsible for the infections of the urinary tract and the best chemical agents for their treatment have been found. The great majority of infections are caused by the «Escherichia coli» in the first place, followed by «Proteus, SPP». «In vitro» the ideal chemical agents for treatment were: Nitroxolin, Tobramycin, Nalidixic Acid, and Gentamicin, for the gram-negative germs and Nitroxolin, Rifampicine and Cefazolin for the gram-positive ones.